2019
DOI: 10.1187/cbe.18-08-0171
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction and Learning Outcomes in Asynchronous Online Lecture Videos

Abstract: Our study identified online lecture video styles that improved student engagement and satisfaction, while maintaining high learning outcomes in online education. We presented different lecture video styles with standardized material to students and then measured learning outcomes and satisfaction with a survey and summative assessment. We created an iterative qualitative coding scheme, “coding online asynchronous lectures” (COAL), to analyze open-ended student survey responses. Our results reveal that multimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 52 publications
(96 reference statements)
9
117
0
3
Order By: Relevance
“…For example, asynchronous delivery of online lecture video can be effective and engaging for students, but the method of presentation impacts student engagement and satisfaction (Choe et al, 2019).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, asynchronous delivery of online lecture video can be effective and engaging for students, but the method of presentation impacts student engagement and satisfaction (Choe et al, 2019).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Creating an engaging online environment can be done with any of the above delivery modes, but how this is done will likely differ. For example, asynchronous delivery of online lecture video can be effective and engaging for students, but the method of presentation impacts student engagement and satisfaction (Choe et al., 2019). Choe and colleagues tested 6 methods of online lecture video creation in an upper division physiology course and found that although scores on summative assessments did not differ following the 6 styles, student satisfaction and rating of effectiveness of styles did (Choe et al., 2019).…”
Section: Designing Better Online Courses: Integrating Active Learningmentioning
confidence: 99%
“…For years, many medical schools, including our own, have been recording lectures and making them available for students online—a style of teaching that has been proven popular and effective since it allows students to learn at their own pace and in their own time [ 7 , 8 ]. As remote teaching has become the norm, students in medical schools such as ours can adapt more readily, as we are already familiar with the platforms and format of recorded lectures.…”
Section: Adaptability: Our Responsiveness In Unprecedented Timesmentioning
confidence: 99%
“…Creating an engaging online environment can be done with any of the above delivery modes, but how this is done will likely differ. For example, asynchronous delivery of online lecture video can be effective and engaging for students, but the method of presentation impacts student engagement and satisfaction (Choe et al, 2019). Choe and colleagues tested 6 methods of online lecture video creation in an upper division physiology course and found that although scores on summative assessments did not differ following the 6 styles, student satisfaction and rating of effectiveness of styles did (Choe et al, 2019).…”
Section: Inclusive Teaching Through Management Of Attitudes and Expecmentioning
confidence: 99%
“…For example, asynchronous delivery of online lecture video can be effective and engaging for students, but the method of presentation impacts student engagement and satisfaction (Choe et al, 2019). Choe and colleagues tested 6 methods of online lecture video creation in an upper division physiology course and found that although scores on summative assessments did not differ following the 6 styles, student satisfaction and rating of effectiveness of styles did (Choe et al, 2019). Instructors may want to focus on video design that highlights personal connection and engagement as these factors were rated most highly by students (see Choe et al, 2019 for more details and examples); these are also important aspects of inclusive classrooms.…”
Section: Inclusive Teaching Through Management Of Attitudes and Expecmentioning
confidence: 99%